The Influence of System Quality and User Personality on the Behavioural Intention towards Virtual Reality Usage in Tourism - Pratisto, Eko Harry (Curtin University, 2022)
Virtual reality has great potential to promote tourism by providing a simulated experience of potential travel destinations. An extensive literature review revealed that the role of system quality and user’s personality remained under-explored. This thesis addresses these gaps by investigating the factors that influence an individual’s intention to travel after experiencing VR. Two studied were conducted to empirically test the hypothesised relations, shedding light on the complex role of system quality and user personality.